Designing a CGE-based economic assessment mechanism from a tourism perspective: A case of post-COVID-19 recovery in Northeast Asia - Lin, Wen-Cheng; Yu, Yi-Ying Linda (Edelweiss Applied Science and Technology, 2025)
This study aims to establish an economic assessment mechanism that evaluates the impacts of epidemic disasters from the perspective of the tourism industry. Using the Computable General Equilibrium (CGE) framework, we design a simulation mechanism to quantify losses caused by the COVID-19 pandemic. The Global Trade Analysis Project (GTAP) model incorporates tourism as a shock factor to simulate two scenarios: zero-COVID and coexistence, based on control measures implemented between 2020 and 2022 in the context of sustainable tourism development. Results indicate that economic indicators across all regions declined comprehensively under the assumption of rising unemployment. Specifically, (1) GDP losses are often underestimated but closer to observed outcomes; (2) accommodation and food service sectors exhibit greater output declines than transportation sectors; and (3) Northeast Asia experiences more severe output losses than the global average. Zero-COVID policies must be cautiously designed to prevent unemployment, particularly for smaller economies that are highly vulnerable to labor immobility. This study provides a tourism-oriented assessment mechanism for epidemic responses. It suggests that mitigating losses requires substituting cross-border consumption with trade in goods, restoring supply-side capacity, and avoiding excessive discriminatory restrictions on international travelers.